The Geopolitical Codes of The United States Decision to Relocate Its Embassy to Israel from Tel Aviv to Jerusalem (POLITEA, 2019)
Geopolitical Codes of the United Dtates Policy to Relocate Its Embassy to Israel to Jerusalem. Trump’s policy to relocate the US embassy triggered Palestinian mass protests and wider political tension. Ten of thousands Palestinian took part in Gaza protests. Protests are also took place on The West Bank, where the focus was the embassy move. A mass protests turned violent, as Israeli troops responded with rifle fire. This policyraises strong reactions from world leaders. This paper aims to explain the geopolitical codes of The United States Policy : who are the allies or the supporter of the US policy in case of US embassy relocation and who are the enemies that against the US policy. We will find out whether this United States agenda will succeed in leading world opinion and influencing other countries' foreign policies and the consequences of what the United States will give to its supporters and opponents of its policies.